SELF EFFICACY TINGGI MENINGKATKAN SELF REGULATION LEARNING PADA MAHASISWA KEPERAWATAN UNIVERSITAS TRIBHUWANA TUNGGADEWI - Rosdiana, Yanti; Hastutiningtyas, Wahidyanti Rahayu (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Online lectures are one way to carry out the teaching and learning process during the Covid-19 period. This online learning process makes students have to have high self-efficacy in order to succeed in learning with the online/online method. Self-regulated learning is certainly needed where students have to monitor themselves both in terms of thoughts, feelings and behavior. The purpose of the study was to determine the relationship between self-efficacy and self-regulated learning in nursing students at Tribhuwana Tunggadewi University, Malang. The design used is analytic observation with a cross sectional approach. The research was conducted in January 2021. The instrument was a modified questionnaire, namely Self Efficacy with General Self Efficacy Scale (GSE) and Self Regulated Learning with Online Self Regulated Learning Questionnaire (OSLQ). The sampling technique was purposive sampling with 73 students as respondents. The results of data analysis were carried out using the sperman-rank test and there was a significant relationship between self-efficacy and Self-Regulated Learning for semester 1 students at Fikes University Tribhuwana Tunggadewi Malang 2021 with p = 0.000 (p 0.05) and r = 0.411. During online lectures, nursing students are expected to improve self-regulated learning by developing self-efficacy by implementing time management during online lectures, making independent learning plans and being active in searching for sources or literature to facilitate understanding of online lectures.